Comparison of Dichotic Consonant- Vowel test results between right handed and left handed adults with normal hearing - Mitra Janghorban; Leila JalilvandKarimi; Mohamad Hosein Nilforoush; Seyed Mehdi Tabatabaei (مجله پژوهش در علوم توانبخشی, 2013)
Introduction: According to the previous studies, left hemisphere of the brain has specialized for language processing. The relation between handedness and the brain hemispheres is very obvious. In more than 95% of right- handed people and 70% of left- handed people the left hemisphere is responsible for language processing generally. A few studies have investigated the relationship between handedness and the brain hemispheres by means of Dichotic Consonant- Vowel ( DCV ) test. The aim of the present study is to investigate the results of DCV test in right- handed and left- handed adults with normal hearing.